2020
DOI: 10.1002/pa.2349
|View full text |Cite
|
Sign up to set email alerts
|

Impact of overconfidence among finance managers on forecasted market returns: Evidence from India

Abstract: The current article studies the impact of overconfidence among finance managers on forecasted market returns in India. Overconfidence among finance managers is measured using a standardised questionnaire and data is collected from February, 2017 to October, 2018. Snowball sampling is used as the sampling technique to collect data from 200 finance managers. The secondary data for the study is collected from the Centre for Monitoring Indian Economy (CMIE) Prowess. Overconfidence among finance managers is modelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Puetz and Ruenzi (2009) found that positive past performance leads to overconfidence. Mundi and Nagpal (2020) examined the overconfidence among finance managers and its influence on predicted market return. They found that finance managers' overconfidence affects their forecasted market returns, also they demonstrated that managers have miscalibrated the situation, it is only due to their overconfidence, not their skills.…”
Section: Behavioral Biases and Investment Decision-makingmentioning
confidence: 99%
“…Puetz and Ruenzi (2009) found that positive past performance leads to overconfidence. Mundi and Nagpal (2020) examined the overconfidence among finance managers and its influence on predicted market return. They found that finance managers' overconfidence affects their forecasted market returns, also they demonstrated that managers have miscalibrated the situation, it is only due to their overconfidence, not their skills.…”
Section: Behavioral Biases and Investment Decision-makingmentioning
confidence: 99%